EDUKASI INOVATIF CEGAH PENYALAHGUNAAN NARKOBA: PENINGKATAN PENGETAHUAN REMAJA MELALUI MEDIA AUDIOVISUAL - Eka Diana Permatasari; Yessy Pramita Widodo; Khodijah Khodijah; Novi Aprilia Kumala Dewi; Arif Rakhman; Nurhakim Yudhi Wibowo; Feny Dwi Anggraeni; Susi Muryani; Deni Irawan; Wisnu Widyantoro; Ratna Widhiastuti; Agus Budianto; Firman Hidayat; Syarifudin Bakhtiar; Agung Laksana Hendra Pamungkas (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2025)
Drug abuse is an increasing global health concern, with adolescents being among the most vulnerable populations. Insufficient knowledge and unengaging educational methods highlight the need for innovative educational approaches, such as audiovisual media. This community service activity aimed to enhance adolescents' understanding of the dangers of drug abuse. The activity was conducted through innovative education, utilizing a five-minute educational video for 88 adolescents aged 12-18 years. The implementation methods included audiovisual education, interactive discussions, and pre- and post-education knowledge assessments. Results indicated an improvement in participants' knowledge regarding the dangers of drug abuse. This program is expected to serve as an initial step in improving community health, particularly among adolescents. The program has a positive impact on strengthening health through increased knowledge and acts as a preventive measure against drug abuse in adolescents. Keywords: Audiovisual, Education, Knowledge, Drugs, Adolescents